Bad bosses and self‐verification: The moderating role of core self‐evaluations with trust in workplace management. Issue 2 (28th June 2019) - Booth, Jonathan E.; Shantz, Amanda; Glomb, Theresa M.; Duffy, Michelle K.; Stillwell, Elizabeth E.
Abstract: Who responds most strongly to supervisor social undermining? Building on self‐verification theory (Swann, 1983, 1987), we theorize that employees with positive views of the self (i.e., higher core self‐evaluations [CSEs]) who also maintain higher trust in workplace management are more likely to experience heightened stress and turnover intentions when undermined. We argue that this subset of employees (high CSE, high trust) are more likely to feel misunderstood when undermined by their supervisor and that this lack of self‐verification partially explains their stronger responses to supervisor undermining. We find initial support for the first part of our model in a study of 259 healthcare workers in the United States and replicate and extend our findings in the second study of 330 employees in the United Kingdom. Our results suggest that the employees Human Resources often wishes to attract and retain—employees with high CSE and high trust in workplace management—react most strongly to supervisor social undermining.